2008
DOI: 10.1176/ps.2008.59.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Public Psychiatrists' Reports of Their Own Recovery-Oriented Practices

Abstract: Although some recovery-oriented practices were used infrequently (for example, facilitating peer advocacy), a number of important practices were endorsed at relatively high levels. The association of recovery-oriented practices with awareness of recovery concepts suggests that education and advocacy may promote such practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Therefore, an alternate approach is advocacy, seeking to create awareness of recovery-oriented practices and to promote dialogue about how to implement them. This approach is supported by a recent study I conducted with a colleague in which we found that psychiatrists with more awareness of recovery concepts were more likely to employ recovery-oriented practices (Ranz & Mancini, 2008).…”
Section: Role In Policy-makingsupporting
confidence: 60%
“…Therefore, an alternate approach is advocacy, seeking to create awareness of recovery-oriented practices and to promote dialogue about how to implement them. This approach is supported by a recent study I conducted with a colleague in which we found that psychiatrists with more awareness of recovery concepts were more likely to employ recovery-oriented practices (Ranz & Mancini, 2008).…”
Section: Role In Policy-makingsupporting
confidence: 60%
“…There is evidence that is it effective (Marshall 2011) and that it supports recovery values (Deegan 2006). However, the accounts of people using mental health services, along with observations and surveys of psychiatric practice, all suggest that it is not fully implemented, with psychiatrists often using persuasion to improve adherence (Seale 2006(Seale , 2007Ranz 2008;Baker 2011). This has also led to a tendency for mental health workers to withhold information about possible adverse effects of medication (Pollock 2004;Chaplin 2007, this journal).…”
Section: Making Shared Decision-making a Realitymentioning
confidence: 99%
“…There is now substantial evidence for the benefits of supporting people in selfmanagement across the whole of medicine, although clinicians may need help to develop the relevant attitudes and skills (Health Foundation 2011). This may be an area where psychiatrists currently feel less confident and less equipped (Ranz 2008). The College's competencybased curriculum for psychiatric training (Royal College of Psychiatrists 2010) explicitly requires trainees to be 'aware of strategies to enhance patient understanding and potential selfmanagement' (p. 57), indicating that this is supported as a future direction for the profession.…”
Section: Alternative Strategiesmentioning
confidence: 99%
“…Focusing on patients’ quality of life and recovery are the real goals. 4 What is astonishing is the paucity of research as to how psychiatry got into this mess in the first place. Perhaps the consultant psychiatrist is perceived as an expensive dinosaur – after all, with the advent of nurse prescribers, is there anything left we can do that cannot be done by someone else?…”
Section: The Need For Actionmentioning
confidence: 99%